Analisis Penerapan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik pada Usaha Mikro Kecil Menengah PT Galang Smart Indonesia - triseptya, ghaliyah nimassita; Zulkifli; Delpiana (PT Bone Jaya Kreatif, 2023)
Guidelines for preparing financial reports for SMEs such as coffee businesses have been prepared by the Financial Accounting Standards Board of the Indonesian Accounting Association (DSAK IAI). The guidelines are called Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). SAK ETAP is a solution for small and medium-sized businesses that have difficulty in applying the current statement of Financial Accounting Standards (PSAK). The purpose of this study was to determine the form of preparation of financial statements that had been made by MSME PT Galang Smart Indonesia and to determine the form of preparation of financial statements in accordance with Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) at MSME PT Galang Smart Indonesia. This study uses a descriptive method using a quantitative approach based on a case study on the 2021 financial statements of PT Galang Smart Indonesia. Indicators of assessment as a form of application of SAK ETAP in this study are financial statements and their components are in accordance with the types and components of financial statements regulated in SAK ETAP.The results of the study indicate that the Financial Statements owned by MSME PT Galang Smart Indonesia have not fully implemented SAK ETAP. financial reports prepared by MSME PT Galang Smart Indonesia in the form of Balance Sheet Reports, Profit/Loss Reports, HPP Reports. The financial statements regulated in the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) are Profit/Loss Statements, Changes in Equity Reports, Balance Sheet Reports, Cash Flow Statements and Notes to Financial Statements